MANAJEMEN ADAPTIF DAN PENGEMBANGAN KREATIVITAS ANAK DI PAUD KARYA BAKTI MEDAN - Lola Srininta; Dhea Amanda, Imma Niani Gulo, Elisa Simatupang, Rotua Simanjuntak, Dinda Aprilia, Nailah Pulungan, A (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the application of adaptive management and the development of creativity in children at PAUD Karya Bakti Medan. Early childhood education is a crucial stage in shaping the foundations of children's cognitive, emotional, social, and creative development. In this context, adaptive management is a strategic approach that can respond to the dynamics of children's needs and real conditions in the field. This study uses a qualitative-descriptive approach with observation, interviews, and documentation techniques to obtain in-depth data. The results show that PAUD Karya Bakti Medan has implemented adaptive management principles through flexible, participatory, and collaborative leadership, as well as support for teacher competency development through continuous training. Children's creativity is developed through art-based activities, although documentation and utilisation of the results of their work still need to be improved. Learning innovation and exploration of children's potential require strengthening in managerial and pedagogical aspects so that learning outcomes are more impactful and sustainable. This study recommends optimising the documentation of children's works and developing more contextual learning strategies to maximise creativity.